THE CONSEQUENCES OF VIOLATING THE IMMUNITY OF CARTHAGINIAN ENVOYS IN THE LIGHT OF LIV. 38.42.7 AND VAL. MAX. 6.6.3 1 - Leraczyk, Izabela (Review of European and Comparative Law, 2018)
The article analyses the casus of beating Carthaginian envoys in 188 BC and the effects that this act exerted on the grounds of international law, sacral norms and, at a later time, on the grounds of criminal regulations laid by the Romans. Those issues are analyzed on the basis of the account by Titus Livius (38.42.7) and Valerius Maximus (6.6.3). The analysis demonstrates that emissaries dispatched to other peoples were protected by immunity and it also indicates the way in which envoys were chosen in the republican Rome, as well as the customs related to their reception. It is also presented in the article what types of behaviour might have been perceived as violations of envoys’ immunity and what sanctions were faced by those perpetrating such acts. On the grounds of ius gentium there was a threat of declaring war, which could be averted only if the perpetrator was delivered to the affected community. On the grounds of sacral law, it was assumed that a deed of that nature entailed sacrilegium, and a blame could not be in any way removed from an individual. However, the whole society could be remitted their guilt by delivering the wrongdoer to the injured party. Further, the text analyzes the proceedings in the case of causing bodily harm to Punic envoys – the actions undertaken by the urban praetor and the procedure of delivering the perpetrators (deditio) to Carthaginians, carried out by the fetiales.